2020
DOI: 10.1111/inm.12807
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative study on the causes and consequences of compassion fatigue from the perspective of nurses

Abstract: Compassion is one of the core elements of nursing care. Continued exposure to patient pain and suffering puts nurses at risk of developing compassion fatigue. The aim of this study was to understand the causes and consequences of compassion fatigue from the perspective of nurses. To this end, a qualitative design based on the hermeneutic phenomenology paradigm was used. Five focus group sessions were held with 43 nursing professionals. Two themes and six sub-themes emerged from the analysis of their discourses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 42 publications
4
34
0
1
Order By: Relevance
“…Based on our review of the literature, this study was the first during the pandemic to identify such a pattern of relationships. While we could not locate similar studies during the pandemic, this result is in agreement with reports prior to the pandemic, which established a strong association between CF, work satisfaction, and nurses' intent to leave their jobs ( Pérez-García et al, 2021 ). For example, in China, job engagement and CF explained nurses' decision to leave their current workplace ( Cao & Chen, 2020 ), while in the US, compassion satisfaction and CF were both associated with increased turnover intention among hospital nurses ( Wells-English et al, 2019 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Based on our review of the literature, this study was the first during the pandemic to identify such a pattern of relationships. While we could not locate similar studies during the pandemic, this result is in agreement with reports prior to the pandemic, which established a strong association between CF, work satisfaction, and nurses' intent to leave their jobs ( Pérez-García et al, 2021 ). For example, in China, job engagement and CF explained nurses' decision to leave their current workplace ( Cao & Chen, 2020 ), while in the US, compassion satisfaction and CF were both associated with increased turnover intention among hospital nurses ( Wells-English et al, 2019 ).…”
Section: Discussionsupporting
confidence: 88%
“…When left unmanaged, CF may have untoward repercussions on nurses' well-being and health, resulting in mental health concerns (e.g., burnout, depression, stress, and anxiety) leading to work impairment ( Pérez-García et al, 2021 ), job dissatisfaction ( Kim et al, 2017 ), and eventual nurse turnover ( Wells-English, Giese, & Price, 2019 ). These conditions could ultimately influence the way nurses provide care, resulting in increased incidence of adverse events, patient errors and missed nursing care, and poorer health service delivery ( Alharbi et al, 2020a , Alharbi et al, 2020b , Alharbi et al, 2020c ; Peters, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, long-term exposure to death situations can cause compassion fatigue (Hotchkiss and Cook-Cottone, 2019), often described as the negative cost of hospice care (Barrett et al, 2019). The negative emotions can cause them to experience low energy levels, difficulty concentrating, unwanted images or thoughts, insomnia, stress, and desensitization, and even potentially substance abuse, depression and suicide in the long term (Pérez-García et al, 2021). The study results showed that 18% of hospice nurses met the criteria for compassionate fatigue and suffered from different degrees of insomnia and depression (Kase et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Kode hermeneutika mencakup sejumlah pertanyaan, teka-teki yang berujung kepada sebuah jawaban yang konkrit. Terdapat pertanyaan yang ditemukan dalam kode hermeneutik dimana jawaban yang satu melahirkan pertanyaan lainnya untuk menunda jawaban awal (Pérez-García et al, 2020). Kode hermeneutik mengandung narasi yang mempertajam isu narasi yang menciptakan sebuah misteri dibalik jawaban.…”
Section: Metode Penelitianunclassified